4. Conceptual Materiality and Sculptural Critique - Vereștiuc Mihai (Sciendo, 2023)
Based on the recent sculptural projects of Mihai Verestiuc, we will establish a conceptual connection of with the practice of post-minimalist sculpture, using as argument certain lines developed by artists such as Joseph Beuys and Rachel Whiteread in their works analysed in this article. The course of the works, in itself, offers us the opportunity to reflect on the assumed responsibility towards the formative impact that any artistic object offers in relation to the environment in which it is produced (social, cultural, economic or political) and that starts from the artist through all the elements implicit of his approach - the concept, the specificity of the material and the space, the socio-cultural reality.